Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.

Does the Gradualness of Leaf Shedding Govern Nutrient Resorption from Senescing Leaves in Mediterranean Woody Plants? (Plant and Soil, 2005)
The resorption of nutrients from senescing leaves is a key component of the nutrient conservation strategy of plants. Despite its relevance, the regulation of the eﬃciency of this process is poorly understood. The aim of this work was to test the hypothesis that species that shed leaves gradually along the year are less eﬃcient reabsorbing nutrients from senescing leaves than species that shed leaves in a short period. N-, P-, and Kresorption-eﬃciencies were measured in 11 Mediterranean species and regressed against an index of the gradualness of leaf shedding. Additionally, the bivariate relations among leaf nutrient content before senescence, nutrient content in senesced leaves, pool of nutrients reabsorbed during senescence, and nutrient resorption eﬃciency, were examined. K-resorption-eﬃciency was markedly lower in species with protracted leaf-shedding, in agreement with the initial hypothesis. This pattern was less signiﬁcant for Nand P-resorption-eﬃciencies. When leaf nutrient content before senescence was high, the amount of nutrients reabsorbed and the amount of nutrients in senesced leaves were high. Consequently, nutrient resorption eﬃciency was unaﬀected by the leaf nutrient status before senescence. It is concluded that the leaf shedding pattern per se inﬂuences nutrient resorption in Mediterranean perennials, irrespective of additional environmental controls. Furthermore, it is suggested that plants diﬀering in nutrient status do not exhibit diﬀerent nutrient resorption eﬃciencies because the nutrient content of leaves before senescence aﬀects the components of resorption eﬃciency in countervailing ways.

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.